2007
DOI: 10.1097/01.tp.0000255319.07499.b7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Extended Donor Criteria and Changes in the Model for End-Stage Liver Disease Score Predict Patient Survival and Primary Dysfunction in Liver Transplantation: A Retrospective Analysis

Abstract: The combination of a liver recipient with worsening Delta-MELD and a potential donor with at least two EDC should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 20 publications
1
48
1
6
Order By: Relevance
“…39 Worsening MELD score or delta-MELD (current MELD-maximum score in the last 3 months) has been shown to impact post-transplant outcome, 40 and one should avoid graft with >1 EDC for such patients. 41 Similar observations by another study on patients with Hepatitis B virus (HBV) related liver disease and MELD >29 showed that downgrading MELD score using anti-HBV drugs improved outcomes of LT compared to emergency LT. 42 In this respect, product of age and delta-MELD less than 1600 may be required for optimal post-transplant outcomes. 43 …”
Section: Model For End-stage Liver Disease and Posttransplant Survivalmentioning
confidence: 70%
“…39 Worsening MELD score or delta-MELD (current MELD-maximum score in the last 3 months) has been shown to impact post-transplant outcome, 40 and one should avoid graft with >1 EDC for such patients. 41 Similar observations by another study on patients with Hepatitis B virus (HBV) related liver disease and MELD >29 showed that downgrading MELD score using anti-HBV drugs improved outcomes of LT compared to emergency LT. 42 In this respect, product of age and delta-MELD less than 1600 may be required for optimal post-transplant outcomes. 43 …”
Section: Model For End-stage Liver Disease and Posttransplant Survivalmentioning
confidence: 70%
“…Foi considerado como disfunção do enxerto (DF) o paciente que apresentou dosagem sérica de ALT acima de 1000 UI/L (DF1); DF2 quando a ALT ficou entre 1001 UI/L e 2499 e DF3 quando a dosagem foi maior que 2500 UI/L. Esta classificação foi adaptada dos critérios de HEISE et al (27) , em 2003. g) DCE DCE ficou como sendo o número de variáveis do doador fora do padrão ideal (12) proposto por SILBERHUMER et al (48) , que variaram de 1 até 5.…”
Section: F) Graus De Disfunção Do Enxertounclassified
“…Alguns autores, no Brasil, procuraram estudar a utilização desse critério de ordenação de gravidade, seja comparando a classificação de Child-Turcotte-Pugh (CTP) mostrando sua validade ou questionando a alocação de órgãos por lista única pela gravidade do doente com doença hepática crônica (6,14,36,47,48,49,50) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In Tector et al, 21 for example, only donor age Ͼ60 yr, as a single variable, had a significant prognostic impact on post-LT graft survival. As explained by Briceno et al, 16,17 Pokorny et al, 2,11 and Silberhumer et al, 22 however, it is the synergic sum of marginal factors, rather than their single contributions, that best predict severe liver preservation injury. In this light, Feng et al, 23 Ioannou, 24 and Burroughs et al 25 have introduced a combination of donor variables in scores for predicting post-LT outcome in their recent works.…”
Section: Discussionmentioning
confidence: 97%